ASSESSING THE IMPACT OF THE JIWA JAGAD JAWI VIDEO ON INDONESIAN CULTURAL AWARENESS AS TOURIST ATTRACTIONS (International Conference on Economics, Business, and Management Research (ICEBMR), 2024)
Indonesia, as one of the largest countries in the world, has a rich culture spread across its seventeen thousand islands. The promotional video Jiwa Jagad Jawi that was launched in 2022 in a theme of rediscovering the mind, body, and soul of Java whilst promoting several destinations in Java, and seeks to show the depth of Javanese culture while promoting its various destinations. This research investigates the impact of videos on awareness of Indonesian culture as a tourist attraction through examining content and audience reactions. Using a qualitative approach, this analysis investigates how the video depicts Indonesian culture, traditions and landscapes, as well as the responses received from global YouTubers who re-uploaded the video. The research results show that Jiwa Jagad Jawi video effectively strengthens Indonesia's cultural heritage, increasing its attractiveness as a tourist destination. Despite various interpretations, the video has emerged as an important influence in shaping perceptions of Indonesian culture and driving tourist behavior. This underlines the importance of digital media in cultural promotion and sustainable tourism development. This comprehensive analysis aims to provide valuable insight into utilizing digital platforms as a powerful tool to foster cultural appreciation and encourage tourism growth in Indonesia.
Keywords: cultural awareness; tourist attractions; YouTube; audience reactions